Feasibility work to inform the design of a randomized clinical trial of wound dressings in elective and unplanned abdominal surgery. Issue 12 (4th August 2016) - ,
Abstract : Background: Designing RCTs in surgery requires consideration of existing evidence, stakeholders' views and emerging interventions, to ensure that research questions are relevant to patients, surgeons and the health service. When there is uncertainty about RCT design, feasibility work is recommended. This study aimed to assess how feasibility work could inform the design of a future pilot study and RCT (Bluebelle, HTA ‐ 12/200/04). Methods: This was a prospective survey of dressings used to cover abdominal wounds. Surgical trainees from 25 hospitals were invited to participate. Information on patient risk factors, operation type and type of wound dressings used was recorded for elective and unplanned abdominal procedures over a 2‐week interval. The types of dressing used were summarized, and associations with operation type and patient risk factors explored. Results: Twenty hospitals participated, providing data from 727 patients (1794 wounds). Wounds were predominantly covered with basic dressings (1203 of 1769, 68·0 per cent) and tissue adhesive was used in 27·4 per cent (485 of 1769); dressing type was missing for 25 wounds. Just 3·6 per cent of wounds (63 of 1769) did not have a dressing applied at the end of the procedure. There was no evidence of an association between type of dressing used and patient risk factors, type of operation, or elective and unscheduled surgery. Conclusion: Based on the findings from this large study of current practice, the pilot study design has evolved. The inclusion criteria have expanded to encompass patients undergoing unscheduled surgery, and tissue adhesive as a dressing will be evaluated as an additional intervention group. Collaborative methods are recommended to inform the design of RCTs in surgery, helping to ensure they are relevant to current practice. Abstract : Relevant background work